Patient age and number of apheresis days may predict development of secondary myelodysplastic syndrome and acute myelogenous leukemia after high‐dose chemotherapy and autologous stem cell transplantation for lymphoma. Issue 4 (10th February 2017) - Ge, Isabell; Saliba, Rima M.; Maadani, Farzaneh; Popat, Uday R.; Qazilbash, Muzaffar H.; Ravi Pingali, Sai; Shah, Nina; Ahmed, Sairah; Bashir, Qaiser; Nieto, Yago; Champlin, Richard E.; Hosing, Chitra
Abstract : BACKGROUND: The goal of our study was to find predictors for the development of secondary myelodysplastic syndrome or acute myelogenous leukemia (s‐MDS/AML) in patients with relapsed or refractory lymphoma who received high‐dose chemotherapy and autologous stem cell transplantation (ASCT). STUDY DESIGN AND METHODS: We conducted a retrospective review of 295 patients with relapsed or refractory lymphoma who had undergone their first stem cell collection and ASCT. Patient, disease, and treatment characteristics were collected. The primary goal of this study was to analyze the association between the number of apheresis days needed to collect the requisite stem cell dose in addition to the previously described factors such as age, sex, number and type of prior chemotherapeutic regimens, disease type and status, and the risk of developing s‐MDS/AML. RESULTS: Twenty‐two patients of 295 were diagnosed with s‐MDS/AML after a median follow‐up of 62 months. Multivariate analysis using a classification and regression tree showed that the incidence of s‐MDS/AML was lowest in patients who were not more than 55 years old at transplantation and in whom the target cell dose was collected in fewer than two apheresis sessions (5‐year cumulative incidence, 1%), whereas incidence was highest in patients who were more than 55 years old at transplantation and who received a transplant more than 21 months after their initial lymphoma diagnosis (5‐year cumulative incidence, 20%). CONCLUSION: Our study defines a subset of relapsed or refractory lymphoma patients who should be closely monitored for development of s‐MDS/AML after high‐dose chemotherapy and ASCT.